Evaluating The Prospects of Financial Performance After Merger at PT Pelabuhan Indonesia (Persero - Kusumaningrum, Indah; Heikal, Jerry (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Port is a gateway which facilitates connection between regions, islands and even continents as well as between nations that can develop the hinterland area behind or also known as the area of influence. Previously, to manage ports in Indonesia, four state-owned ports were formed that play a role in the development and operation of national ports which were divided based on different regions, namely PT Pelabuhan Indonesia I (Persero)/Pelindo I, PT Pelabuhan Indonesia II (Persero)/Pelindo II, PT Pelabuhan Indonesia III (Persero)/Pelindo III, and PT Pelabuhan Indonesia IV (Persero)/Pelindo IV which have their respective operating areas coverage.. The separation of BUMN Ports into several operating areas contributes to the challenges of the national port industry. The merger of SOE Ports is expected to have significant benefits for stakeholders such as the government. This research aims to evaluate the prospect financial performance of PT Pelabuhan Indonesia (Persero) after merger by comparing the financial ratio before and after merger , as well as comparing the financial ratio of PT Pelabuhan Indonesia (Persero) with another 12 Global Port Company using descriptive analysis and K-Means Clustering. The research result shows that the financial performance before merger decreased, the company ‘s financial performance cluster before merger is low (in the 3rd cluster) and yje company financial performance after the merger is stable on the 3rd cluster. Therefore, PT Pelabuhan Indonesia (Persero) need to formulate several strategy to increase their financial performance especially in optimizing their assets and inventory to have more efficient operational to generate higher sales.